Generation of Calibration Chart for Horizontal Cylindrical Fuel Tank - Rungrudesombatkit, Satit (Srinakharinwirot University Engineering Journal, 2021)
This research aimed to create a calibration chart for a horizontal cylindrical fuel tank with the wet calibration method of a 1,300-liter horizontal cylindrical fuel tank that was covered with flat sheets at the ends by using water as a medium for calibration. The calibration had the following steps: 1) establishing criteria for water filling in stages 2) development of a filling steps schedule 3) setting up standards and equipment 4) filling the tank with water to the desired height; and 5) continuous information presentation. The finding revealed that the calibration chart of a horizontal fuel tank, which is derived from the mathematical model between the volume and height of water, can be referenced to create a volumetric scale. The errors and uncertainty in volumetric interpolation were in accordance with the criteria agreed between the company and the customer.